Question about Educational & Reference Software

Set builder form only can be write if u generate a set while following some logic or property ok

Posted on Sep 20, 2008

Assuming the 'standard form' is "slope-intercept", calculate the slope from the equation m = __y2-y1__ =__ 5 - 1__ = __ 4__ = -2

x2-x1 4 - 6 -2

The intercept can be found by substituting either of the two points into the equation y = mx + b

5 = (-2)4 + b

5 = (-8) + b

13 = b

(OR, using the other point, y = mx + b

1 = (-2)6 + b

1 = (-12) + b

13 = b )

Then expressing in general:

**y = (-2) x + 13**

x2-x1 4 - 6 -2

The intercept can be found by substituting either of the two points into the equation y = mx + b

5 = (-2)4 + b

5 = (-8) + b

13 = b

(OR, using the other point, y = mx + b

1 = (-2)6 + b

1 = (-12) + b

13 = b )

Then expressing in general:

Oct 10, 2014 | Educational & Reference Software

The rate of change for the function y=5x+4 is the coefficient 5 that multiplies the independent variable x. For a unit variation of x (x varies by 1) y varies by 5 units.

Between x1=2 to x2=3, y varies from y1=5*2+4=14 to y2=5*3+4=19.

The rate of change is defined as

**(variation in y)/(variation in x)=(19-14)/(3-2)=5**

Between x1=2 to x2=3, y varies from y1=5*2+4=14 to y2=5*3+4=19.

The rate of change is defined as

Sep 28, 2014 | SoftMath Algebrator - Algebra Homework...

8.98=898/100

Both numerator and denominator are multiples of 2:The fraction can be simplified further. Simplifying, you get the irreducible form of the fraction as t 449/50.

Both numerator and denominator are multiples of 2:The fraction can be simplified further. Simplifying, you get the irreducible form of the fraction as t 449/50.

Sep 06, 2014 | Educational & Reference Software

If you are calculating **Integral ((x^3+2)^2* 3x^2*dx) **define X=x^3+2, dX=3.x^2 dx, integral becomes Integral (X^3.dX)=X^3/3=**(1/3)(x^3+2)^3**

If you are calculating** Integral ((x^3+2)^2* 3x^4*dx)**, develop the binomial, and use the rule for the integral of a power to integrate each term in the polynomial of degree 10 that you obtain. **I will leave this for you to do.**

If you are calculating

Dec 15, 2013 | Bagatrix Precalculus Solved Full Version...

1=10^0

10=10^1

100 (2 zeroes after the 1)=1x10^2

1000 (3 zeroes after the 1)=1x 0^3

1000 000 (one million) =1x10^6

1 billion =1 000 000 000 =1x10^9

100 billions =100x 1000 000 000=(1x10^2)x(1x10^9)=

1x(10^2)x(10^9)

Now use the power multiplication rule**(a^n)x[a^m)=a^(m+n)**. Thus

1x(10^2)x(10^9)=1x10^(2+9)=1x10^(11)

**100 billions =1x10^11=10^11**.

10=10^1

100 (2 zeroes after the 1)=1x10^2

1000 (3 zeroes after the 1)=1x 0^3

1000 000 (one million) =1x10^6

1 billion =1 000 000 000 =1x10^9

100 billions =100x 1000 000 000=(1x10^2)x(1x10^9)=

1x(10^2)x(10^9)

Now use the power multiplication rule

1x(10^2)x(10^9)=1x10^(2+9)=1x10^(11)

Sep 10, 2013 | Educational & Reference Software

**Solve (***x*+ 2)(*x*+ 3) = 12.

- It is very common for students to see this type
of problem, and say:

solve to get x = 10 and x = 9. That was easy!"

So, tempting though it may be, I cannot set each of the factors above equal to the other side of the equation and "solve". Instead, I first have to multiply out and simplify the left-hand side, then subtract the 12 over to the left-hand side, and re-factor. Only then can I solve.

- (

(

Jul 17, 2011 | H. B. Enterprises Quadratic Solver

The error may be with the file or the software you are using to open it. Try download a fresh copy of adobe reader and try copying the file again and opening it again.

Mar 27, 2011 | MyHeritage Family Tree Builder

open the form with microsoft paint.select the tool "A" to enter text and eraser to delete text

Dec 31, 2010 | Educational & Reference Software

The tangent of an angle (in a right triangle) is defined to be the length of the side opposite the angle, divided by the length of the side adjacent to the angle (that is not the hypoteneuse). As the angle approaches 90 degrees, the length of the opposite side gets very large and the length of the adjacent side nears 0. At 90 degrees, the length of the adjacent side is 0, and division by 0 is not defined, so the tangent of 90 degrees is not defined.

Nov 26, 2010 | Texas Instruments World of Mathematics...

Use the rule for differentiating products of functions: ()' signifies derivative

(29*sin(2X)*sin(X))'= (29)'*sin(2X)*sin(X) +29* (sin(2X))'*sin(X) +29*sin(2X)*(sin(X))'

But

(29*sin(2X)*sin(X))'= 29*2*cos(2X)*sin(X)+29*sin(2X)*cos(X)

You could also have cast your formula in the form

sin(2X)*sin(X)= 1/2[ cos(2X-X)-cos(2X+X)]=1/2[cos(X)-cos(3X)]

then calculated the derivative of

29/2*[cos(X)-cos(3X)]

which is

29/2*[-si(X) +3*sin(3X)]

The challenge for you is to prove that the two forms are equivalent

29*2*cos(2X)*sin(X)+29*sin(2X)*cos(X)=29/2*[-si(X) +3*sin(3X)]

(29*sin(2X)*sin(X))'= (29)'*sin(2X)*sin(X) +29* (sin(2X))'*sin(X) +29*sin(2X)*(sin(X))'

But

- (29)'=0 derivative of a constant is zero
- (sin(2X))'=cos(2X)*(2X)'=2*cos(2X)
- (sin(X))'=cos(X)

(29*sin(2X)*sin(X))'= 29*2*cos(2X)*sin(X)+29*sin(2X)*cos(X)

You could also have cast your formula in the form

sin(2X)*sin(X)= 1/2[ cos(2X-X)-cos(2X+X)]=1/2[cos(X)-cos(3X)]

then calculated the derivative of

29/2*[cos(X)-cos(3X)]

which is

29/2*[-si(X) +3*sin(3X)]

The challenge for you is to prove that the two forms are equivalent

29*2*cos(2X)*sin(X)+29*sin(2X)*cos(X)=29/2*[-si(X) +3*sin(3X)]

Jun 21, 2010 | Vivendi Excel@ Mathematics Study Skills...

185 people viewed this question

Usually answered in minutes!

×